2019
DOI: 10.1080/20008198.2019.1665768
|View full text |Cite
|
Sign up to set email alerts
|

Targeting hyperarousal: Mantram Repetition Program for PTSD in US veterans

Abstract: Background: Hyperarousal appears to play an important role in the development and maintenance of posttraumatic stress disorder (PTSD) symptoms, but current evidencebased treatments appear to address this symptom type less effectively than the other symptom clusters. The Mantram Repetition Program (MRP) is a meditation-based intervention that has previously been shown to improve symptoms of posttraumatic stress disorder (PTSD) and may be especially helpful for hyperarousal. If MRP is an effective tool for decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…RCTs of the MRP have also documented reduced PTSD diagnostic prevalence, reduced PTSD symptom severity, and improved self-efficacy for managing PTSD symptoms (Bormann et al 2008 , 2013b , 2018 ; Oman and Bormann 2015 ). RCTs of the MRP have furthermore documented significant and favorable treatment effects on stress-related mental health outcomes that include hyperarousal, insomnia, burnout, quality of life, and depression (Barger et al 2015 ; Beck et al 2017 ; Bormann et al 2008 , 2013b , 2018 ; Crawford et al 2019 ; Yong et al 2011 ). In non-randomized studies, the MRP has been linked to reduced stress in VA staff, family caregivers in the USA, and nursing students in Korea (Bormann et al 2006c , 2009 ; Kang and Yong 2019 ).…”
Section: Mantram Repetition Programmentioning
confidence: 99%
See 1 more Smart Citation
“…RCTs of the MRP have also documented reduced PTSD diagnostic prevalence, reduced PTSD symptom severity, and improved self-efficacy for managing PTSD symptoms (Bormann et al 2008 , 2013b , 2018 ; Oman and Bormann 2015 ). RCTs of the MRP have furthermore documented significant and favorable treatment effects on stress-related mental health outcomes that include hyperarousal, insomnia, burnout, quality of life, and depression (Barger et al 2015 ; Beck et al 2017 ; Bormann et al 2008 , 2013b , 2018 ; Crawford et al 2019 ; Yong et al 2011 ). In non-randomized studies, the MRP has been linked to reduced stress in VA staff, family caregivers in the USA, and nursing students in Korea (Bormann et al 2006c , 2009 ; Kang and Yong 2019 ).…”
Section: Mantram Repetition Programmentioning
confidence: 99%
“…In such longer time periods, the accumulated benefits of engaging in MRP practices and integrating adherence to them into daily routines can foster additional attentional and psychosocial factors that causally mediate outcomes of interest. Thus, statistical mediation analyses of evidence from randomized trials of the MRP, investigating changes over 5 to 8 weeks and sometimes longer, have supported mediation of benefits by at least five factors: increased trait mindfulness, strengthened self-efficacy, improved coping, reduced hyperarousal, and enhanced psychospiritual well-being (Bormann and Carrico 2009 ; Bormann et al 2012 , 2014a ; Crawford et al 2019 ; Oman and Bormann 2015 ). Evidence from RCTs also indicates that gains in mindful awareness from the MRP intervention are mediated by frequency of mantram repetition (Bormann et al 2014a ).…”
Section: Mantram Repetition Programmentioning
confidence: 99%
“…Hyperarousal symptoms can be specifically addressed in a variety of ways (e.g., meditation) (Crawford, Talkovsky, Bormann, & Lang, 2019). Some treatments targeting an overstimulated sympathetic nervous system may have undesirable side effects.…”
Section: The Underlying Brain Circuitry Malfunctionmentioning
confidence: 99%
“…Empirical evidence for such an approach is provided by observed improvements in brain regions associated with cognitive processing and arousal in patients with PTSD, social anxiety disorder, and major depressive disorder who received cognitive behaviour therapy (Aupperle et al, 2013; Månsson et al, 2013; Ritchey, Dolcos, Eddington, Strauman, & Cabeza, 2011). Additionally, targeted reduction of physiological hyperarousal is also likely indicated and may be treated with pharmaceutical methods, relaxation strategies, mindfulness (Crawford, Talkovsky, Bormann, & Lang, 2019), exercise (Babson et al, 2015), and/or cognitive restructuring. Interestingly, mindfulness‐based stress reduction (MBSR) has demonstrated significant reductions in self‐reported PTSD symptoms, attention, depression, emotion regulation, and general hyperarousal symptoms in various PTSD patient populations (Boyd, Lanius, & McKinnon, 2018); however, no trials of MBSR in patients with PTSD have reported on the effects on sleep disturbance.…”
Section: Clinical Implications Future Research Directions and Summarymentioning
confidence: 99%